A Map Of Uses Of Impact Evaluation Approaches - Delahais, Thomas; Devaux-Spatarakis, Agathe; Jégou, François; Rousseau, Karen (Journal of MultiDisciplinary Evaluation, 2024)
Background: Not all evaluation practitioners are experts in the diversity of impact evaluation approaches. How can these approaches be made clear and accessible? How can practitioners be better able to choose the relevant one? A collaborative project was initiated in 2021 to address these questions, and involved the French Development Agency’s evaluation officers, external evaluators, and public-sector co-designers. Purpose: This article presents the development of a visual tool designed to facilitate meaningful discussions between evaluation officers and project managers regarding an array of available impact evaluation approaches. In our view, the positive reception of the map of uses of impact evaluation approaches within and beyond the Agence française de développement underscores the significance of anchoring discussions on evaluation scope and methodologies in real-world evaluation uses. Setting: Not applicable. Intervention: Not applicable. Research design: Not applicable. Data collection and analysis: Not applicable. Findings: Not applicable.